Estrategias didácticas para el proceso enseñanza aprendizaje de geometría y medida en la Unidad Educativa Fiscomisional Manuel José Rodríguez parroquia Malacatos - Loja - Sánchez Benavides, Nayelly Guisella (2024)
The didactic strategies favor positively the teaching and learning of abstract concepts present in the subject of Geometry. Thus, the objective of the research was to analyze the didactic strategies for the teaching-learning process of Geometry in the “Unidad Educativa Fiscomisional Manuel José Rodríguez” in Malacatos - Loja. For this, it was carried out a study with descriptive exploratory scope of non-experimental type supported in a mixed approach, from the qualitative part a systematic documentary review was performed about the didactic strategies used for the teaching of Geometry; and, from the quantitative part, data collection instruments were used in the classes developed by the teachers, the bibliographic review allowed sustaining the conceptual categories and characterizing the didactic strategies used for the development of the teaching-learning process of Geometry. The field study made it possible to identify the didactic strategies used by the teachers at the school unit for the teaching of Geometry. The results showed that didactic strategies are important mainly because they facilitate the transmission and reception of knowledge, generate meaningful learning, encourage group work, improve academic performance, motivate students and generate knowledge in a simpler way, in addition, it was determined that teachers mainly use three didactic strategies located in order of percentage of application these are: Van Hiele's geometric reasoning, use of concrete materials and Gamification, they also showed that there is an almost null application of software for the resolution of tasks, being the main limitation for its application the internet connectivity. Keywords: Didactic strategies, teaching, learning and Geometry.